Effects of small for gestational age status on mortality and major morbidities in ≤750 g neonates. (May 2020) - Poryo, Martin; Maas, Sebastian; Gortner, Ludwig; Geipel, Martina; Zemlin, Michael; Löffler, Günther; Meyer, Sascha
Abstract: Background: Controversy exists regarding the impact of small for gestational age (SGA = birth weight < 10th percentile) status on mortality and major morbidities. Aim: To assess the effects of SGA on mortality and major morbidities in ≤750 gram (g) neonates. Study design: Retrospective (01/2005–12/2017), single center study at a tertiary NICU. Subjects: SGA neonates ≤ 750 g. Outcome: Effect of SGA status on mortality and major morbidities. Results: 183 infants were enrolled. 103 (56.3%) were non-SGA (mean gestational age 25 + 1 weeks ± 9.9 days, mean birth weight 662.6 ± 75.2 g), and 80 (43.7%) SGA (mean gestational age 26 + 6 weeks ± 14.0 days, mean birth weight 543.9 ± 114.7 g). Mortality was 24.1% (non-SGA: 30/103 (29.1%), SGA: 14/80 (17.5%); p  = 0.08). Univariable logistic regression analysis revealed a significant protective effect of SGA status on pneumothoraces (OR 0.28, 95%-CI [0.11–0.69]), IVH (≥3) (OR 0.38; 95%-CI [0.15–0.67]), and seizures (OR 0.09, 95%-CI [0.01–0.76]), but NEC (≥2a) occurred more frequently in SGA neonates ( p  = 0.024). Multiple logistic regression analysis found SGA status to negatively influence ROP (≥3) (OR 2.87, 95%-CI [1.14–7.23]) and need for home monitoring (OR 2.38, 95%-CI [1.05–5.41]). Other major morbidities (IVH, PVL, RDS, BPD, NEC, FIP, sepsis, hearing impairment) and mortality rates were not significantly affected, but distinct organ-specific patterns were seen. Conclusion: SGA had negative effects on the rate of severe ROP and the need for home monitoring, but other major morbidities as well as mortality rates were not significantly affected. In the future, it will be important to delineate underlying pathophysiological mechanisms that contribute to this pattern. Highlights: Our study demonstrated that small for gestational age (SGA) status does not have a negative impact on mortality in neonates with a birth weight ≤ 750 grams. Our study suggests that SGA status exerts different, organ-specific effects with regard to major morbidities in neonates with a birth weight ≤ 750 grams SGA status increased the risk for major morbidities, most importantly retinopathy of prematurity, and the need for home monitoring in ≤ 750 grams neonates.